Laryngeal chondronecrosis after radiation therapy in a dog. (30th November 2017) - Bertran, J.; Martinez, M.; Breit, M.; McLoughlin, M. A.; Ham, K. L.; Warry, E.; Wavreille, V.
Abstract : A 5‐year‐old pug presented with a soft tissue swelling on the ventral neck and moderate stridor with associated respiratory effort. This patient received hypofractionated radiotherapy for metastatic upper lip mast cell tumour and to the submandibular lymph nodes 6 months before presentation. Oral examination showed moderate elongation of the soft palate, stage III laryngeal collapse with only the right laryngeal saccule mildly everted and exuberant pale epiglottal and left pharyngeal mucosa. Staphylectomy, resection of the epiglottal mucosa and left arytenoid lateralisation were performed. One day after surgery, temporary tracheostomy was performed after respiratory distress due to the severe laryngeal and pharyngeal oedema. A third oral exam showed pale and redundant caudal pharyngeal mucosa obstructing the rima glottis, soft and collapsible arytenoid cartilage with pale mucosa and bilateral everted laryngeal saccules. Permanent tracheostomy was elected and laryngeal cartilage biopsies were taken. Histologic diagnosis showed cartilage necrosis and abundant tissue oedema. The patient was euthanased 1 week later.